Laryngeal Lymphoma: The High and Low Grades of Rare Lymphoma Involvement Sites. (22nd July 2014) - Azzopardi, Charles Paul; Degaetano, James; Betts, Alexandra; Farrugia, Eric; Magri, Claude; Refalo, Nicholas; Gatt, Alexander; Camilleri, David J.
Abstract : The larynx is an extremely rare site of involvement by lymphomatous disease. We present two cases of isolated laryngeal high-grade and another low-grade lymphoma, together with a literature review of laryngeal lymphoma management.